DETERMINAN TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI TAHUN 2019-2021 - Thasya, Syam Hafiva; Sudirgo, Tony (Jurnal Paradigma Akuntansi, 2024)
This study was conducted with the aim to analyze the effect of tax avoidance on between profitability, leverage and firm size in manufacturing companies sector consumer goods listed on the Indonesian Stock Exchange (IDX). The sample of this study used in this study by utilizing 93 data consisting of 31 manufacturing companies in the consumer goods sector with the research population selected from the 2019-2021 period used purposive sampling method. The software for data processing used in this study is Eviews 12. Based on this research, the results show that profitability has a negative effect on tax avoidance. Meanwhile, leverage has no effect on tax avoidance and firm size has no effect on tax avoidance.